Treasury of Greek mythology : classic stories of gods, goddesses, heroes & monsters - Napoli, Donna Jo, 1948-; Balit, Christina (Washington : National Geographic Society, 2011)
Presents illustrated retellings of classic Greek myths, sharing the stories of Zeus, Aphrodite, Apollo, Athena, Helen of Troy, Perseus, and Medusa, with sidebars for each god, goddess, hero, and monster that link the tales to constellations, history, geography, and culture, and including profiles, a family tree, and other resources.
Gaia, mother Earth -- Uranus, father heaven -- Cronus, Titan king -- Zeus, king of the gods -- Hestia, goddess of the hearth -- Poseidon, god of the seas -- Athena, goddess of wisdom -- Hades, god of the underworld -- Demeter, goddess of the harvest -- Apollo, god of music -- Artemis, goddess of the hunt -- Hera, goddess of marriage -- Hephaestus, god of metalworking -- Aphrodite, goddess of love and beauty -- Hermes, messenger of the gods -- Ares, god of war -- Helios, Sun god -- Selene, goddess of the Moon -- Dionysus, god of wine -- Perseus, the ill-fated hero -- Orion, the hunter -- Heracles, the hero who became immortal -- Jason, wanderer of the seas -- Theseus, the king of Athens -- Helen, the lethal beauty.
Includes bibliographical references (p. 186-187) and index.
860
Accelerated Reader AR
Keywords: Mythology, Greek -- Juvenile literature